2015
DOI: 10.1038/srep07610
|View full text |Cite
|
Sign up to set email alerts
|

A panel of five serum miRNAs as a potential diagnostic tool for early-stage renal cell carcinoma

Abstract: Circulating microRNAs (miRNAs) are emerging as clinically useful tools for cancer detection; however, little is known about their early diagnostic impact on RCC. The levels of 754 serum miRNAs were initially determined using a TaqMan Low Density Array in two pooled samples from 25 RCC and 25 noncancer controls. Markedly dysregulated miRNAs in RCC cases were subsequently validated individually by qRT-PCR in another 107 patients and 107 controls arranged in two sets. The serum levels of miR-193a-3p, miR-362 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
114
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(121 citation statements)
references
References 42 publications
4
114
0
3
Order By: Relevance
“…It has been clearly demonstrated that miRNAs steadily existed in plasma [8] and the regulation of circulating miRNAs was closely associated with cancer types and disease progression [9,10]. In RCC diagnosis, it has been previously found that miR-210, miR-378, miR-451, miR-193a-3p, miR-362, miR-572, miR-28-5p, and miR-378 [11][12][13][14] all had the potential to be the plasma or serum biomarker for RCC. However, these biomarkers lack a high accuracy in RCC diagnosis with single detection and it is necessary to combine 2 or more members to improve the diagnostic accuracy, which would significantly increase the testing costs in clinical practice.…”
Section: Introductionmentioning
confidence: 97%
“…It has been clearly demonstrated that miRNAs steadily existed in plasma [8] and the regulation of circulating miRNAs was closely associated with cancer types and disease progression [9,10]. In RCC diagnosis, it has been previously found that miR-210, miR-378, miR-451, miR-193a-3p, miR-362, miR-572, miR-28-5p, and miR-378 [11][12][13][14] all had the potential to be the plasma or serum biomarker for RCC. However, these biomarkers lack a high accuracy in RCC diagnosis with single detection and it is necessary to combine 2 or more members to improve the diagnostic accuracy, which would significantly increase the testing costs in clinical practice.…”
Section: Introductionmentioning
confidence: 97%
“…The heterogeneity of mutations within tumours, which results in different subclones that evolve differently, is a major obstacle to clinical translation 235,236,238,239 . Intratumour heterogeneity of DNA methylation might, however, not be as pronounced as intratumour heterogeneity of genomic changes.…”
Section: Prognosismentioning
confidence: 99%
“…[65][66][67][68][69][70][71][72][73][74][75][76] Specifically, relatively few studies, including only one multicentre study 67 , have been conducted, and most studies did not perform an internal validation with a training and validation set or even an internal validation approach, such as bootstrapping or cross-validation. Moreover, all studies except one used serum as the source of RNA despite plasma being the blood component of choice since the release of miRNAs from blood cells such as the miRNA-enriched platelets into serum occurs during the coagulation process.…”
Section: [H1] Biofluid Mirnas In Kidney Cancermentioning
confidence: 99%
“…In addition, different strategies were applied for normalizing RT-qPCR data and contrasting results regarding the regulation of miR-378, as example, were reported already in three studies. 68,72,74 All studies conducted to date were primarily focused on the diagnostic objective of discrimination between patients with RCC and healthy control subjects.…”
Section: [H1] Biofluid Mirnas In Kidney Cancermentioning
confidence: 99%
See 1 more Smart Citation